(untitled) (Academia Journal of Medicine, 2024)
Background: Thrombotic thrombocytopenic purpura (TTP) is a rare and life-threatening condition characterized by microthrombus formation due to a deficiency of ADAMTS13, which cleaves von Willebrand factor multimers. This deficiency leads to widespread microangiopathic hemolytic anemia and multiple organ involvement, particularly affecting the brain, heart, and kidneys. TTP can present atypically and poses a diagnostic challenge, especially in young patients with neurological symptoms and thrombocytopenia. Early diagnosis and prompt initiation of plasma exchange therapy (PEX) and steroids are critical to reduce mortality. Case Report: A 17-year-old male presented in an altered state with weakness in the right upper arm and bilateral lower limbs for 4 days. He had a history of fever and convulsions 4 days prior, with two previous convulsive episodes in the last two years, both of which had resolved without neurological deficits. On examination, the patient was febrile, tachycardic, and drowsy, with left gaze palsy and significant weakness in the right upper limb and both lower limbs. The patient had lost bowel and bladder sensation, and plantar reflexes were bilaterally upgoing.An MRI of the brain with angiogram revealed acute large vessel occlusion in the bilateral anterior cerebral artery (ACA) territory and gliosis in the right middle cerebral artery (MCA) region. Laboratory investigations showed severe thrombocytope nia (platelet count 23k/cumm), anemia (Hb 6.2 g/dL), elevated LDH (1597 U/L), and increased cardiac troponin (35 pg/mL). The patient was diagnosed with TTP and was promptly started on plasma exchange therapy and high-dose steroids. His sensorium improved within 2 days, though weakness persisted. Plasma exchange therapy was continued daily for 11 days, resulting in gradual improvement.